2020
DOI: 10.5937/jemc2002116r
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of entrepreneurial intentions among students and employees

Abstract: The paper tackles the comparison of entrepreneurial intentions among students and employees in Serbia. A t-test was applied to compare individual entrepreneurial orientation dimensions, achievement dimension, and theory of planned behaviour dimensions (including entrepreneurship intention dimension). The analysis also encompassed gender as the subject's control variable. The main conclusions are 1. Risk-taking dimension, Proactiveness, and Achievement have statistically significantly higher average values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Students have the greatest inclination to entrepreneurship, while employees have not shown so much interest. (Rajković et al, 2020) Despite the fact that most research indicates a positive correlation between education and people's propensity for entrepreneurship, there are also studies that indicate that in certain cases education can have negative effects on people's propensity for entrepreneurship. A study conducted by Nabi et al (2010) concluded that people with higher education show lower levels of propensity for entrepreneurship compared to people with secondary or lower education.…”
Section: Entrepreneurial Education and Entrepreneurial Intentionsmentioning
confidence: 99%
“…Students have the greatest inclination to entrepreneurship, while employees have not shown so much interest. (Rajković et al, 2020) Despite the fact that most research indicates a positive correlation between education and people's propensity for entrepreneurship, there are also studies that indicate that in certain cases education can have negative effects on people's propensity for entrepreneurship. A study conducted by Nabi et al (2010) concluded that people with higher education show lower levels of propensity for entrepreneurship compared to people with secondary or lower education.…”
Section: Entrepreneurial Education and Entrepreneurial Intentionsmentioning
confidence: 99%